New features of solid particle erosion damage of control stage blades in supercritical steam turbine. (February 2016) - Cai, Liu-xi; Mao, Jing-ru; Wang, Shun-sen; Feng, Zhen-ping
Reducing solid particle erosion of blades is one of the most urgent problems for high-parameter steam turbine power generation technology. Based on the erosion rate model and particle rebound model of blade materials obtained through accelerated erosion test under high temperature, erosion characteristics of flaky particles in control stage of a typical supercritical steam turbine were systemically studied using three-dimensional numerical simulation method. The erosion mechanism of hard coatings on nozzle suction surface is first revealed, and erosion resistance of boride coating with large oxide particles is validated through high-temperature erosion test. Results show that serious erosion damage of boride coating on the latter half of nozzle suction surface is caused by the combined rebounded impingement of large particles between 1000 µm and 2000 µm after their initial impingement on the nozzle pressure surface and the leading edge of rotating blade. The average particle impingement velocity can reach up to 150–180 m/s, and the impingement angle is in the range of 18°–28°. High-temperature erosion test results show that boride coating will soon broken and fall off under the continuing impact of millimeter-sized particles, which confirms that hard coatings are difficult to resist the high-intensity impingement from these large particles. Therefore, separating particles before entering the nozzle chamber with the employment of an inertial separator should be the optimal choice for improving the erosion resistance of turbine. The results of this study enrich the types of blade erosion damage and provide a new idea for reducing erosion damage of control stage blades.